A POLYGLOT’S STRATEGIES IN LEARNING FOREIGN LANGUAGES: A CASE STUDY - Martiningsih, Widiana; Mukarto, Fransiscus Xaverius (LLT Journal: A Journal on Language and Language Teaching, 2024)
Polyglots typically have specific learning strategies to learn new languages. This study aims to tap into the learning strategies employed by a female Indonesian who speaks six languages, namely Javanese, Minang, Malay, Indonesian, English, and Russian, and is currently learning three additional languages, namely French, Spanish, and Arabic. This case study used an interview to gain a deeper understanding of the learning strategies. The interview revealed that the participant used direct and indirect strategies in a balanced proportion. Further discussion also revealed that she used cognitive strategy and social strategy most frequently, i.e. in the form of practice and social interaction, respectively. The case study is expected to serve as a reference for language learners seeking to learn new languages.